Extracellular vesicle species differentially affect endothelial cell functions and differentially respond to exercise training in patients with chronic coronary syndromes. (8th May 2020) - Kränkel, Nicolle; Strässler, Elisabeth; Uhlemann, Madlen; Müller, Maja; Briand-Schumacher, Sylvie; Klingenberg, Roland; Schulze, P Christian; Adams, Volker; Schuler, Gerhard; Lüscher, Thomas F; Möbius-Winkler, Sven; Landmesser, Ulf
Abstract: Background: Extracellular vesicles are released upon cellular activation and mediate inter-cellular communication. Individual species of extracellular vesicles might have divergent roles in vascular homeostasis and may show different responses to therapies such as exercise training. Aims: We examine endothelial effects of medium-size and small extracellular vesicles from the same individual with or without chronic coronary syndrome, and in chronic coronary syndrome patients participating in a four-week high-intensity interval training intervention. Methods: Human aortic endothelial cells were exposed to medium-size extracellular vesicles and small extracellular vesicles isolated from plasma samples of study participants. Endothelial cell survival, activation and re-endothelialisation capacity were assessed by respective staining protocols. Extracellular vesicles were quantified by nanoparticle tracking analysis and flow cytometry. Extracellular vesicle microRNA expression was quantified by realtime-quantitative polymerase chain reaction. Results: In patients with chronic coronary syndrome ( n  = 25), plasma counts of leukocyte-derived medium-size extracellular vesicles were higher than in age-matched healthy controls ( n  = 25; p  = 0.04) and were reduced by high-intensity interval training ( n  = 15; p  = 0.01 vs baseline). Re-endothelialisation capacity was promoted by medium-size extracellular vesicles from controls, but not by medium-size extracellular vesicles from chronic coronary syndrome patients. High-intensity interval training for 4 weeks enhanced medium-size extracellular vesicle-mediated support of in vitro re-endothelialisation. Small extracellular vesicles from controls or chronic coronary syndrome patients increased endothelial cell death and reduced repair functions and were not affected by high-intensity interval training. Conclusion: The present study demonstrates that medium-size extracellular vesicles and small extracellular vesicles differentially affect endothelial cell survival and repair responses. This equilibrium is unbalanced in patients with chronic coronary syndrome where leukocyte-derived medium-size extracellular vesicles are increased leading to a loss of medium-size extracellular vesicle-mediated endothelial repair. High-intensity interval training partially restored medium-size extracellular vesicle-mediated endothelial repair, underlining its use in cardiovascular prevention and therapy to improve endothelial function.